Oral and Palatal Dentition of Axolotl Arises From a Common Tooth-Competent Zone Along the Ecto-Endodermal Boundary - Soukup, Vladimír; Tazaki, Akira; Yamazaki, Yosuke; Pospisilova, Anna; Epperlein, Hans-Henning; Tanaka, Elly M.; Cerny, Robert (Frontiers in Cell and Developmental Biology, 2021)
Vertebrate dentitions arise at various places within the oropharyngeal cavity including the jaws, the palate or the pharynx. These dentitions develop in a highly organized way, where new tooth germs are progressively added adjacent to the initiator center, the first tooth. At the same time, the places where dentitions develop, house the contact zones between the outer ectoderm and the inner endoderm and this co-localization has instigated various suggestions on the roles of germ layers for tooth initiation and development. Here we study development of the axolotl dentition, which is a complex of five pairs of tooth fields arranged into the typically tetrapod outer and inner dental arcades. By tracking the expression patterns of odontogenic genes, we reason that teeth of both dental arcades originate from common tooth-competent zones, one present on the mouth roof and one on the mouth floor. Progressive compartmentalization of these zones and a simultaneous addition of new tooth germs distinct for each prospective tooth field subsequently control the final shape and composition of the axolotl dentition. Interestingly, by following the fate of the GFP-labelled oral ectoderm, we further show that, in three out of five tooth field pairs, the first tooth develops right at the ecto-endodermal boundary. Our results thus indicate that a single tooth-competent zone gives rise to both dental arcades of a complex tetrapod dentition. Further, we propose that the ecto-endodermal boundary running through this zone should be accounted for as a potential source of instruction factors instigating the onset of the odontogenic program.